A description of the Chilean Psychology from analysis of two national journals - González de Requena, Juan Antonio (Revista de Psicología, 2013)
The style of psychology as a discipline has become increasingly complex as a result of the subdivision of specialties and the multiplication of approaches. This article provides a mapping of current Chilean Psychology, based on research papers of two indexed publications: Revista de Psicología, published by the Universidad de Chile, and Psykhe, published by the Universidad Católica de Chile. Themes, methodologies, disciplinary selfpresentation, ontology, subjects and research problems are described through content analysis. The results of this study clarify the findings of previous research on the perception of psychology in American academia (Biglan, 1973; Kolb, 1981), which consider it a soft and pure discipline, that is, concrete and reflexive.